Cutaneous Toxicity Associated With Enfortumab Vedotin: A Real-Word Study Leveraging U.S. Food and Drug Administration Adverse Event Reporting System - Yang, Hui; Yu, Xiaojia; An, Zhuoling (Frontiers in Oncology, 2022)
Introduction: Enfortumab vedotin (EV) has demonstrated to have a significant response rate in early phase trials and is known for its tolerable side-effect profile. Emerging case reports have raised awareness of cutaneous toxicities which maybe potentially a fatal complication. Objective: To assess the potential relevance between enfortumab vedotin (EV) and cutaneous toxicities reports through data mining of the the U.S. Food and Drug Administration (FDA) adverse event reporting system (FAERS). Methods: Data from January 1, 2019 to June 30, 2021 in the FAERS database were retrieved. Information component (IC) and reporting odds ratio (ROR) were used to evaluate the association between EV and cutaneous toxicities events. Results: EV was significantly associated with cutaneous toxicities in the database (ROR 12.54[10.17-15.46], IC 2.75[2.49-3.02], Middle signal). And significant association was detected between EV and all the cutaneous adverse effects (AEs) except erythema and dermatitis allergic. Stevens-Johnson syndrome occurred 15 times and toxic epidermal necrolysis occurred 17 times as frequency for EV compared to all other drugs in the database (ROR=15.78 and ROR=17.96). All groups that limited the gender and age showed significant association between EV and cutaneous toxicities. Conclusions: Significant signal was detected between EV use and cutaneous toxicities. Notablely, Stevens-Johnson syndrome and toxic epidermal necrolysis were significantly associated with EV use.